Educational and Methodological textbook for practical classes on hygiene: textbook for use in educational institutions implementing the main professional educational programs of higher education at the specialty level in the areas of training 31.05.01 "Medical business", 33.05.01 "Pharmacy", 31.05.03 "Dentistry" - Shashina, E. A. Ekaterina Andreevna (Tutorial, 2020)
This textbook is devoted to the assessment principles of various environmental factors, as well as the body's response to their effects. A large number of tasks helps to master the practical skills of hygienic diagnostics, which are the basis for the formation of doctor professional competencies of any specialty. The textbook is for students of the medical, stomatological and pharmacy faculties of Medical University, studying in English.